2016
DOI: 10.1255/jnirs.1211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Solids of Curry Soup Containing Coconut Milk by near Infrared Spectroscopy

Abstract: The aim of this research was to perform a feasibility study of the potential of near infrared (NIR) spectroscopy to evaluate the total solids content of instant curry soups containing coconut milk; these included green curry, red curry, massaman curry and panang curry. The soup samples were collected from mixing tanks, water adjusting tanks, ultra-high temperature process line and laminated cartons.Adjusted samples were made from the same recipe as in the processing line but with the total solids increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…With total solids content (dry matter), we found the relation between actual dry matter and NIR-predicted dry matter to be linear. 9 This indicated that the dry matter and soluble solids ( Brix) were not in agreement. This was because the dry matter was proportional with water content but the soluble solids were only the matter that dissolved in the curry liquid.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…With total solids content (dry matter), we found the relation between actual dry matter and NIR-predicted dry matter to be linear. 9 This indicated that the dry matter and soluble solids ( Brix) were not in agreement. This was because the dry matter was proportional with water content but the soluble solids were only the matter that dissolved in the curry liquid.…”
Section: Resultsmentioning
confidence: 98%
“…Each homogenized sample was transferred into a quartz cup with a 64 mm diameter and 50 mm length and was scanned through the quartz base of the cup by FT-NIR spectrometer (MPA, Bruker, Ettlingen, Germany) in diffuse reflection mode at a wavenumber between 12,500-3600 cm À1 with a nominal resolution of 16 cm À1 resolution following Sirisomboon and Nawayon. 9 All experiments were performed at room temperature (25 AE 1 C). Each sample was scanned in duplicate.…”
Section: Near Infrared Scanningmentioning
confidence: 99%
“…Sirisomboon and Nawayon 12 reported the performance of the broad-based model for prediction of total solids using the same samples set that it was not better than the individual models of specific curry soup. However, the broad-based calibration had a better coverage of the calibration range and more samples.…”
Section: Resultsmentioning
confidence: 99%
“…The NIR scanning method for the homogenized samples was the same as what reported in Sirisomboon and Nawayon. 12 Each sample was scanned through quartz under the cup (64 mm in diameter and 50 mm in height) using a FT-NIR spectrometer (MPA, Bruker, Ettlingen, Germany) in diffuse reflection mode at a wavenumber between 12,500 and 3600 cm À1 with a resolution of 16 cm À1 . All experiments were performed at room temperature (25 AE 1 C).…”
Section: Nir Spectral Acquisitionmentioning
confidence: 99%
“…Table 2 gives a brief synopsis of different studies that attempted to analyze coconut milk constituents using spectroscopy. These studies have suggested that NIR could be a proper alternative method to measure instant soups’ pH and total solids with coconut milk as the primary ingredient in the production lines for process control and quality assurance [ 65 ]. Thus, spectroscopic methods have proved to be more rapid and accurate.…”
Section: Resultsmentioning
confidence: 99%